Epitaxial strain and interface effects on the magnetoelastic behaviour of Dy/Ho and Dy/Lu superlattices - Benitoa, L; Roky, K; Ciria, M; Arnaudas, J; de la Fuente, C; del Moral, A; Ward, R; Wells, MR; Matheny, A (2004)
The basal plane magnetoelastic stress, Bγ,2, of Dy 16/Ho22, Dy14/Lu30 and Dy 21/Lu11 (0001) superlattices is investigated. For Dy 16/Ho22 we obtain Bγ,2 (12 T, 0 K) = 0.4GPa, while for Dy21/Lu11 and Dy21/Lu 11 it amounts 0.33 and 0.9 GPa, respectively. In the first case, the value obtained is explained in terms of the known values of B γ,2 for bulk Dy and Ho, including small interface and strain contributions, whereas in the Dy/Lu samples, Bγ,2 have large non-bulk contributions. The differences in epitaxial compression and in electronic structure for both kind of superlattices can explain these results. © 2004 Elsevier B.V. All rights reserved.